Debating terrorism in a political transition: Journalism and democracy in Tunisia. (November 2020) - Høigilt, Jacob; Selvik, Kjetil
In March 2015, in the midst of a political transition, Tunisia was rocked by a terrorist attack at the Bardo Museum in downtown Tunis in which 21 people were killed. How did Tunisian journalists manage the tension between a heightened sense of insecurity and the country's uncertain democratic development? This article analyses journalistic commentary on the causes and implications of terrorism four years into the transition sparked by the Arab uprisings. It provides an empirically nuanced perspective on the role of journalism in political transitions, focusing on journalists as arbitrators in public debate. We argue that influential Tunisian journalists fell back on interpretive schema from the Ben Ali era when they tried to make sense of the Bardo attack, thus facilitating the authoritarian drift of the Tunisian government at the time. They actively contributed to the non-linearity of a political transition, despite enjoying real freedom of speech.